COVID-19 Disease and Dermatomyositis: A Mini-Review - Qian, Jie; Xu, Hui (Frontiers in Immunology, 2022)
The pandemic of coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has instituted a large number of deaths and there is still no effective treatment. The COVID-19 can induce a systemic inflammatory response and its clinical manifestations are diverse. Recently, it has been reported that COVID-19 patients may develop myositis and interstitial pulmonary disease similar to dermatomyositis (DM), especially the rapidly progressive interstitial lung disease associated with MDA5+ DM with poor prognosis and high mortality, posing a challenge for early identification. The suppression of the autoimmune system can protect COVID-19 patients by preventing the production of inflammatory cytokines. This article attempts to explore the possibility of a relationship between COVID-19 and DM in terms of potential pathogenesis, clinical features and to analyze the therapeutic effect of immunosuppressive drugs that commonly use for the treatment of DM on COVID-19 strategies.